2007
DOI: 10.1111/j.1399-3046.2007.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal transplant in children with previous inferior vena cava thrombosis

Abstract: Our experience with renal transplantation in children with inferior vena cava thrombosis is presented in this study. Of the 238 children who have received renal transplants at our institution, four had IVC thrombosis (discovered during pretransplant evaluation: three patients; found at surgery: one patient). The pretransplant US evaluation diagnosis of IVC thrombosis in three patients was confirmed by transjugular retrograde cavography. There were no signs of hypercoagulability or IVC thrombosis symptoms prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 13 publications
4
31
0
Order By: Relevance
“…This is also strongly supported by other reports of renal transplantation with thrombosis of the IVC [2][3][4]. A corollary of this recommendation is that there also needs to be careful preoperative joint planning for the transplantation by the pediatric surgeon and nephrologist.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…This is also strongly supported by other reports of renal transplantation with thrombosis of the IVC [2][3][4]. A corollary of this recommendation is that there also needs to be careful preoperative joint planning for the transplantation by the pediatric surgeon and nephrologist.…”
supporting
confidence: 58%
“…The articles cited above [1][2][3][4] account for 14 patients receiving kidney transplants and with preexisting IVC thrombosis. One patient that was described in two separate articles was counted as one, while another patient was included that had severe, but not complete, IVC obstruction [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent case reports in the literature have, however, suggested that successful transplantation may be possible in this technically challenging group of small children [5,6]. One such report proposes utilisation of small, deceaseddonor (DD) renal allografts (age range 0.7-6 years), speculating that such organs may enhance patient survival and provide either long-term renal function or a bridge to a larger renal allograft transplant at a later date [5].…”
Section: Introductionmentioning
confidence: 99%
“…One such report proposes utilisation of small, deceaseddonor (DD) renal allografts (age range 0.7-6 years), speculating that such organs may enhance patient survival and provide either long-term renal function or a bridge to a larger renal allograft transplant at a later date [5]. In contrast, a more recent study reports successful outcomes in four children who received adult-sized kidneys, two of which were from living-related donors (LRD) [6].…”
Section: Introductionmentioning
confidence: 99%